Television journalism on the COVID-19 disaster in Indonesia: conditions, perceptions and production process - Musfialdy; Dadang Rahmat Hidayat; Siti Karlinah; Uud Wahyudin (Penerbit Universiti Kebangsaan Malaysia, 2024)
COVID-19 (Coronavirus Diseases 2019) is a group of viruses from the subfamily Orthocronavirinae in the Coronaviridae family and the order Nidovirales. In Indonesia, dozens of journalists and television editors were exposed to Covid-19, people were stressed, and some even died as a result. The Covid-19 pandemic also caused an increase in people's information needs at that time. This study aims to analyze the conditions, perceptions, and production processes of television journalism during the COVID-19 pandemic in Indonesia, especially on iNews TV, and Metro TV. This research uses an interpretive/subjective paradigm with a constructive approach. This research uses a qualitative case study research methodology. The conclusion of this study is that the condition of Television Journalism during the Covid-19 Pandemic in Indonesia experienced disruption and change. The condition of the television industry experienced a great and deadly disruption. The production process pattern has not changed, but the production process has experienced a very significant change. In the midst of the pros and cons of Covid-19 information, the perception of journalists and television editors remains on data findings in the field that are verified by valid and reliable sources. The positive impact of the Covid-19 pandemic is accelerating the process of convergence of information and communication technology for journalists and television editors. In addition, a journalist is required to have many skills.